(untitled) (Global Journals of Research in Engineering, 2016)
ECG (electrocardiograph) is test that measures the electrical activity of the heart. In an ECG test, the electrical impulses were made while the heart is beating and then it records any problems with the heart#x2019;s rhythm and the conduction of the heart beat through the heart which may be affected by underlying heart disease. In this project different signal processing techniques which are in Time-Frequency Domain and Auto-Correlation will be analyze and later, it will be classify to predict the patient#x2019;s heart condition whether it is healthy or not Apart of that, this project also used three types of method for automatic classifications which are Signal Analysis Technique, Pattern Recognition and Automatic Classification. MATLAB will be used as a computerized of ECG problems. In MATLAB, the data were analyzed and classified